2021
DOI: 10.1136/bmj.n168
|View full text |Cite
|
Sign up to set email alerts
|

Sport associated dementia

Abstract: Prevention remains the only cure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…43 In addition to these primary prevention measures, interventions targeted towards risk mitigation among former rugby players with already accumulated head impact exposures might also be considered, including the development of specialist brain health clinics. 44 A strength of our study is the inclusion of a relatively large number of former rugby players and, importantly, a matched general population comparison group, with outcomes derived from comprehensive electronic health records. As such, potential biases were minimised.…”
Section: Figurementioning
confidence: 99%
“…43 In addition to these primary prevention measures, interventions targeted towards risk mitigation among former rugby players with already accumulated head impact exposures might also be considered, including the development of specialist brain health clinics. 44 A strength of our study is the inclusion of a relatively large number of former rugby players and, importantly, a matched general population comparison group, with outcomes derived from comprehensive electronic health records. As such, potential biases were minimised.…”
Section: Figurementioning
confidence: 99%
“…Formally established in 2015, CTE is a tauopathy defined by its distinct irregular spatial pattern of abnormal tau accumulation in neurons and astroglia around small blood vessels at the base of sulci of the cortex [ 7 ]. Specific mechanisms, including the progressive nature of CTE and additional factors contributing to the pathological development, remain largely unestablished [ 6 , 8 ]. Kriegel and colleagues [ 9 ] proposed the axonal and microvascular injuries which lead to persistent neuroinflammation and metabolic disruption that are sustained due to mTBI may trigger another ‘pathological cascade’ that leads to the development of CTE in at-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no treatment has been validated by clinical trials to be used for the management of CTE [ 5 ]. Experts have suggested looking at other similar neurodegenerative conditions [ 6 ]. Tau targeting therapies intended to modify disease progression in tau pathologies are still under investigation, with symptomatic management remaining the primary intervention strategy for tauopathies.…”
Section: Introductionmentioning
confidence: 99%
“…[5] When it comes to neurocognition, recent research has suggested an association between concussions during a sports career and long-term neurodegenerative conditions, such as dementia. [6] Also, scientific evidence shows that retired professional rugby players are associated with small to moderate impairments in cognitive function (e.g. attention, memory, and concentration) when compared with agematched controls.…”
Section: Health Challenges After Retirement From Professional Rugbymentioning
confidence: 99%